Racism toward the Roma through the affordances of Facebook: bonding, laughter and spite. (July 2019) - Breazu, Petre; Machin, David
This article carries out a multimodal critical discourse analysis (MCDA) of a Romanian Facebook page where comments are made in response to a shared news-clip showing a Roma wedding which clearly invites ridicule. It has been documented that there are well-established discourses representing the Roma as criminal, uneducated, dirty, immoral, and as resisting assimilation into wider society. This Facebook page offers the opportunity to explore which discourses are used in 1500 posts to represent the Roma. We show that the affordances of Facebook open-up the mixing of humor, venting of frustration, extreme racism and sexual violence as those posting entertain each other, create bonds and overtly call out the Roma and others who are believed to be part of a conspiracy against ordinary Romanians. We argue that these newer patterns of representing the Roma are related to the rise of extreme right-wing populist ideology across Europe and beyond. An ideology where direct, simple and violent solutions are required.